IMPLEMENTASI MODEL PEMBELAJARAN SMALL GROUP DISCUSSION SEBAGAI UPAYA MENINGKATKAN PRESTASI BELAJAR MEMBUAT MINUMAN NON ALKOHOL (BUGARIS, 2024)
This research is a type of classroom action research (Classroom Action Research). This research aims to improve the learning achievement of class The data collection methods used are observation, writing and documentation. Research design starts from planning, action, observation and reflection. The application of this learning model starts with the teacher explaining the material, the teacher gives discussion questions to students. Students think about the topic of the story and make notes about initial ideas. Next, the teacher forms students into groups. After that, class discussion. Students and teachers respond to the presenter's answers. The final step is for students to submit assignments. The success indicator for this research is that 80% of students passed the KKM. Based on research data, it can be seen that in the pre-cycle there were 53% (17) students who had completed the KKM, then in cycle I there were 56% (18) students who had completed the KKM, then in cycle II there were 65.6% (21) students who had completed the KKM and in cycle III there were 93.7% (30) students completed the KKM. The success of the research is in accordance with the success indicators obtained during cycle III, namely 93.7% of students completed the KKM or more than 80% of students completed the KKM.